Fear Conditioning Downregulates Rac1 Activity in the Basolateral Amygdala Astrocytes to Facilitate the Formation of Fear Memory - Liao, Zhaohui; Tao, Yezheng; Guo, Xiaomu; Cheng, Deqin; Wang, Feifei; Liu, Xing; Ma, Lan (Frontiers in Molecular Neuroscience, 2017)
Astrocytes are well known to scale synaptic structural and functional plasticity, while the role in learning and memory, such as conditioned fear memory, is poorly elucidated. Here, using pharmacological approach, we find that fluorocitrate significantly inhibits the acquisition of fear memory, suggesting that astrocyte activity is required for fear memory formation. We further demonstrate that fear conditioning downregulates astrocytic Rac1 activity in basolateral amygdala (BLA) in mice and promotes astrocyte structural plasticity. Ablation of astrocytic Rac1 in BLA promotes fear memory acquisition, while overexpression or constitutive activation of astrocytic Rac1 attenuates fear memory acquisition. Furthermore, temporal activation of Rac1 by photoactivatable Rac1 (Rac1-PA) induces structural alterations in astrocytes and in vivo activation of Rac1 in BLA astrocytes during fear conditioning attenuates the formation of fear memory. Taken together, our study demonstrates that fear conditioning-induced suppression of BLA astrocytic Rac1 activity, associated with astrocyte structural plasticity, is required for the formation of conditioned fear memory.